(untitled) (Revista Espinhaço, 2023)
The southern fields are sensitive environments, and over the years it has suffered a considerable decrease in area, mainly to give way to forestry silviculture and monocultures. In addition, as they are predominantly grassy vegetation, they are widely used by livestock. Thus, our objective was to evaluate the environmental impacts of the presence and management of forestry silviculture and livestock areas through the richness and abundance of benthic aquatic macronivertebrates in streams of the Wildlife Refuge Campos de Palmas PR. For this, ten streams with four different physiognomies were sampled. To verify the environmental quality, the BMWP and EPT indices were used, in addition to the verification of the presence of emerging pollutants. The results demonstrate that the presence of forestry areas and cattle management have the lowest values of BMWP and EPT. This demonstrates the environmental fragility in the areas of fields that have extensive cattle ranching. The other points obtained satisfactory indices in water quality.